Stability Of High Rise Building - Tan Mei Chen (School of Environmental Engineering, University Malaysia Perlis, 2016)
To evaluate the linear and nonlinear static analysis of steel frame structure. To compare the lateral displacement of the steel frame structures under the consideration with and without the wind load. To compare the lateral displacement of the steel frame structure with different types of bracings system under the consideration of wind load. To validate SAP 2000 computer software for displacement of steel frame structure.